A Training on Tempeh Processing for Dharma Wanita Persatuan Members of LPKA Kelas II Jakarta - Rianita Pramitasari; Tati Barus; Rory Anthony Hutagalung; Cynthia Angela (Institute for Research and Community Services, 2022)
The practice of social distance and the work-from-home policy due to the Covid-19 pandemic has made activities to improve the skills of Dharma Wanita Persatuan (DWP) members in Lembaga Pembinaan Khusus Kelas II Jakarta which are routinely carried out limited. Online training on making soybean tempeh is one solution to continue carrying out skill-building activities. Soybean tempeh is an Indonesian fermented food made from soybeans. Tempe is one cheap and readily available protein source in Indonesia. In addition, the consumption of tempeh can provide health benefits, such as increasing the immune system. This community service aims to provide online education about tempeh, the benefits of consuming tempeh, and training on its production to women who are members of DWP LPKA Kelas II Jakarta. The community service was carried out by sending them a kit containing ingredients to make soybean tempeh, providing instructions for tempeh processing and discussion facilities in a WhatsApp Group, providing online training synchronously with Zoom, and monitoring and evaluating the tempeh produced. From the implementation of the community service, participants have successfully made tempeh that is healthy, hygienic, and of good taste. To conclude, this community service has been successfully implemented and provides benefits for the participants.